Complete Genome Sequence of Human Echovirus 20 Strain 812/YN/CHN/2010, Associated with Severe Hand-Foot-and-Mouth Disease - Zhao, Yilin (Genome Announc, 2017)
Human echovirus 20 (E-20) belongs to the Human enterovirus B (HEV-B) species and is often detected in nonpolio enterovirus cases of acute flaccid paralysis. We determined the complete genome of strain 812/YN/CHN/2010, isolated from a child with severe hand-foot-and-mouth disease in Yunnan, China, in 2010.